Apocynin attenuates cholesterol oxidation product-induced programmed cell death by suppressing NF-κB-mediated cell death process in differentiated PC12 cells. (October 2015) - Lee, Da Hee; Nam, Yoon Jeong; Lee, Chung Soo
Abstract: Cholesterol oxidation products are suggested to be involved in neuronal degeneration. Apocynin has demonstrated to have anti-inflammatory and anti-oxidant effects. We assessed the effect of apocynin on the cholesterol oxidation product-induced programmed cell death in neuronal cells using differentiated PC12 cells in relation to NF-κB-mediated cell death process. 7-Ketocholesterol and 25-hydroxycholesterol decreased the levels of Bid and Bcl-2, increased the levels of Bax and p53, and induced loss of the mitochondrial transmembrane potential, release of cytochrome c and activation of caspases (-8, -9 and -3). 7-Ketocholesterol caused an increase in the levels of cytosolic and nuclear NF-κB p65, cytosolic NF-κB p50 and cytosolic phospho-IκB-α, which was inhibited by the addition of 0.5 μM Bay11-7085 (an inhibitor of NF-κB activation). Apocynin attenuated the cholesterol oxidation product-induced changes in the programmed cell death-related protein levels, NF-κB activation, production of reactive oxygen species, and depletion of GSH. The results show that apocynin appears to attenuate the cholesterol oxidation product-induced programmed cell death in PC12 cells by suppressing the activation of the mitochondrial pathway and the caspase-8- and Bid-dependent pathways that are mediated by NF-κB activation. The preventive effect appears to be associated with the inhibitory effect on the production of reactive oxygen species and depletion of GSH. Highlights: Apocynin. Inhibits formation of reactive oxygen species and depletion of GSH. Inhibits NF-κB activation. Suppresses the mitochondrial pathway and the caspase-8- and Bid-dependent pathways. Attenuates cholesterol oxidation product-induced apoptosis in PC12 cells.